If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
Y+(5/2)*y-((7/3)*y) = 5/12 // - 5/12
Y+(5/2)*y-((7/3)*y)-(5/12) = 0
Y+(5/2)*y+(-7/3)*y-5/12 = 0
Y+1/6*y-5/12 = 0
x naleu017Cy do R
x in (-oo:+oo)
| 3(-2)+y=-5 | | 2(-2)-3x=-7 | | Ln(-8+3a)=ln(a+6) | | (4-w)(3w+8)=0 | | 5x^2-61x+12=0 | | 4/3x-1=5/2x+4 | | 2h^2+3h-11=-6h-6 | | -12=3(4c+5) | | (8/9)-2 | | 2x+5y=9 6x+9y=10 | | 1/4(20-4a)=6-8 | | 9x/9=72 | | 4p+3q=4.50 | | 6=-2/7z | | (x^2+9x+20)/(x+4) | | 30(5)+30=y | | (3b^7+2b^6+36b^5)/9b | | (3b^7+2b^6+36b^5)/9x | | (3b^7+2b^6+36b^5)/96 | | 30x=25x+25 | | (12v^3+18v^2+3v)/6v | | ln(x+4)-ln(x-2)=6 | | -4+3=y | | -2x-1=-x+3 | | 5x+17=-33 | | (2x)+(x+35)+x=775 | | -2(1)+1=y | | 1-2=y | | n^2+8n-15=0 | | x-2=-2x+1 | | f(x)=-2x^2+2x-3 | | (9+8i)(9+3i)= |